DESIGN AND ANALYSIS OF 4-CYLINDER PISTON AND CONNECTING ROD ASSEMBLY - P. Santhi Priya, M. Harsha Vardhan (International Journal of Advanced Science and Technology, 2020)
The piston of an IC engine is to receive the impulse from the expanding gas and to transmit the energy to the crankshaft via the connecting rod. The piston must also dissipate a large amount of heat from the combustion chamber to the cylinder walls. The aim of this present work is to Design; Assemble the Piston, Connecting Rod; Crankshaft for a 4-stoke air-cooled Engine by theoretical calculations & also to perform the simulation of this mechanism. Modelling of mechanism is carried out Pro/Engineering software & Analysis is performed in ANSYS. Structural analysis and steady state thermal analysis is performed to calculate displacements & thermal stresses under static loads, Vibration response of structure i.e. (natural frequencies & mode shapes) is also checked by using modal analysis and lastly we perform RBD of mechanism to check the behaviour of structure.